Polacy na Syberii – dawniej i dziś - Czerwieniec-Ivasyk, Marta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Siberia is a territory that is mainly associated with exiles. Meanwhile, it was also a place of voluntary settlement of Poles. After the Treaty of Riga, some of them returned to the reviving homeland, Siberia became the house for others. The life of Poles in Soviet Russia was not easy. Polishness was slowly taken away from people. In the post war years, admitting to Polishness resulted in repression of undertaking higher studies or holding managerial positions. After the fall of the USSR, numerous Polish diaspora organizations were reborn there. Largely descendants of Polish settlers between 19 th and 20 th century are still cultivating traditions and attachment to Polish culture.
Poles in Siberia – formerly and today
Keywords: Siberia; exile; Poles; repatriation